Pelatihan Muhadloroh: Strategi Pengembangan Kemampuan Public Speaking Siswa SDN Windu Karangbinangun Lamongan - Rofi’i, Muhammad Arwani; Ulfiyatin, Anis; Yuniarti, Fani Firda; Kumalasari, Ratna Dewi; Amelia, Siti Aisyah (Bale Pengabdian: Journal Of Community Service (BPJCS), 2025)
Elementary school years represent a crucial developmental stage that requires optimal stimulation across various domains, particularly in social development. Self-confidence, as a key element in character formation, is not innate but can be cultivated through social interaction and experience. Many students face difficulties adapting to new environments, leading to low confidence, anxiety, and fear of speaking in public. To address these challenges, a Muhadloroh training program was implemented to strengthen public speaking skills among students of SDN Windu, Karangbinangun. This program employed the Participatory Action Research (PAR) method, actively involving students in every stage, including observation, mentoring, and direct practice. Activities included training as a master of ceremonies (MC), delivering speeches, and creating motivational chants. The results demonstrated significant improvements in students’ courage, creativity, and communication skills. Therefore, Muhadloroh training is proven effective in fostering self-confidence, enhancing public speaking abilities, and developing communicative and confident student character.